EXPERIMENTAL VERIFICATION OF THE EFFECTIVENESS OF COMPUTER NETWORK TRAINING BASED ON NETWORK MODELING - Bidaibekov Е.Ы.; Shekerbekova Ш.Т.; Zhabayev Е.Х. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses the effectiveness of teaching computer networks to future computer science teachers based on network modeling. The experiment was conducted on the basis of the Institute of Mathematics, Physics and Informatics of the Abai Kazakh National Pedagogical University and the Kazakh National Women’s Pedagogical University. Methods and techniques for organizing and conducting practical work on teaching computer networking to future teachers of computer science on the basis of network modeling are described. Analysis of the results of experimental work is presented graphically in the form of tables, diagrams. The pedagogical experiment was conducted in three stages: defining, formative, final. The following research methods were used during the experimental work: analysis, generalization, systematization, observation, questionnaire, testing, research and generalization of pedagogical experience. As a result of experimental work, the effectiveness of the developed methodology for training in computer networks based on network modeling is tested.